2016
DOI: 10.1007/s10535-016-0610-x
|View full text |Cite
|
Sign up to set email alerts
|

The poplar ARGOS-LIKE gene promotes leaf initiation and cell expansion, and controls organ size

Abstract: We identified Populus nigra auxin-regulated gene involved in organ size (PnARGOS)-LIKE encoding one of organ size related (OSR)-proteins in black poplar which is homologous to AtARGOS and AtARGOS-LIKE genes of Arabidopsis thaliana. ABRE-like, G-box, GATA and Ibox motifs were discovered in the promoter region of poplar ARGOS-LIKE gene. In wild type aspen (Populus tremula) plants, ortholog of PnARGOS-LIKE gene (PtrARGOS-LIKE) was noticeably expressed in the actively dividing and expanding young leaves and calli,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…To further investigate whether organ enlargement in the transgenic plants resulted from increased cell division or increased cell expansion, we counted the number of cells in leaves and examined cell area. We found that PagARGOS ‐OE plants had a greater number of cells in leaves, leading to leaf enlargement, contrary to a previous study which reported that constitutive expression of the PnARGOS‐LIKE gene increased size of individual cells (Kuluev et al ., 2016). The differences may come from the different methods used for measurements and growth condition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To further investigate whether organ enlargement in the transgenic plants resulted from increased cell division or increased cell expansion, we counted the number of cells in leaves and examined cell area. We found that PagARGOS ‐OE plants had a greater number of cells in leaves, leading to leaf enlargement, contrary to a previous study which reported that constitutive expression of the PnARGOS‐LIKE gene increased size of individual cells (Kuluev et al ., 2016). The differences may come from the different methods used for measurements and growth condition.…”
Section: Discussionmentioning
confidence: 99%
“…AtARGOS and its homologues are mainly regulated by auxin, ethylene and cytokinin (Feng et al ., 2011; Hu et al ., 2003; Rai et al ., 2015; Wang et al ., 2009, 2010). In the woody plant Populus nigra , ARGOS ( PnARGOS )‐ LIKE , which is homologous to AtARGOS and AtARL , is reported to increase the size of leaves by increasing cell expansion; however, the effect of PnARGOS on secondary xylem development was not explored (Kuluev et al ., 2016). The ARGOS family is also involved in response to abiotic stresses (Ahmed et al ., 2022; Guo et al ., 2014; Rai et al ., 2015; Shi et al ., 2015; Zhao et al ., 2017).…”
Section: Introductionmentioning
confidence: 99%
“…initiation in Arabidopsis and Poplar (Hu et al 2003;Kuluev et al 2016). Besides, we observed a higher phytomer number in both transgenic lines 30 days onwards under greenhouse (Figure 2B).…”
Section: Auxin-regulated Gene Involved In Organ Size (Argos) Inhibiti...mentioning
confidence: 60%